Do women have poorer outcomes following total knee replacement?. Issue 9 (September 2015) - Mehta, S.P.; Perruccio, A.V.; Palaganas, M.; Davis, A.M.
Summary: Objective: To investigate whether women have poorer pain and functional outcomes following total knee replacement (TKR) and to investigate factors that may contribute to this poorer outcome. Methods: In a cohort of 494 people, outcomes were the Pain and Function/Daily Activity subscales of the Knee Injury and Osteoarthritis Outcome Score (KOOS) at 6 and 12 months post-surgery. Sequential multivariable regression analyses evaluated the following independent variables: (1) sex; (2) sex and age; (3) sex, age and pre-surgery score for respective outcome measures; and, (4) model 3 and body mass index (BMI), education, low back pain (LBP), depression, comorbidities, and symptomatic joint count. Results: The sample included 323 women and 171 men. Women were significantly worse on several factors pre-surgery: pain: 39.0 vs 44.9, P  = 0.002; function: 47.7 vs 55.0, P  < 0.0001; depression 5.6 vs 4.7, P  = 0.006; obesity (BMI ≥30): 54.2 vs 36.3%, P  = 0.0002; and, symptomatic joint count: ≥4: 61.3 vs 44.4%, P  = 0.002. Women had worse outcomes for pain (72.2 vs 76.1, P  = 0.04) and function (75.2 vs 80.5, P  = 0.007) at 6 months. This effect was attenuated by adding pre-surgery pain/function. However, the magnitude of the association of pre-surgery pain/function was reduced when LBP, depression, BMI, education level, joint count and comorbidity count were added suggesting association with pre-surgery pain and function. Twelve month results were similar. Conclusion: Women appear to have worse outcomes than men possibly due to a putative pre-operative profile across many factors. Consideration of TKR when impairments in pain and function are less severe along with interventions that address mood and comorbidity may improve outcomes for women having TKR.